Antenatal Corticosteroids in Preterm Small-for-Gestational Age Infants: A Systematic Review and Meta-Analysis - BLANKENSHIP, Stephanie A. (Am J Obstet Gynecol MFM, 2020)
OBJECTIVE: To estimate the effect of antenatal corticosteroid (ACS) administration on neonatal mortality and morbidity in preterm small-for-gestational age (SGA) infants through a systematic review and meta-analysis. DATA SOURCES: A predefined, systematic search was conducted through Ovid Medline, Embase, Scopus, Cochrane Database of Systematic Reviews (CDSR), Cochrane Central Register of Controlled Trials, World Health Organization International Clinical Trial Registry Portal, and ClinicalTrials.gov yielding 5,324 articles from 1970–2019. STUDY ELIGIBILITY CRITERIA: Eligible studies compared neonatal morbidity and/or mortality among SGA infants delivered preterm who received ACS to those who did not. STUDY APPRAISAL AND SYNTHESIS METHODS: The primary outcome was neonatal mortality. Secondary outcomes were respiratory distress syndrome (RDS), necrotizing enterocolitis (NEC), intraventricular hemorrhage and/or periventricular leukomalacia (IVH and/or PVL), bronchopulmonary dysplasia or chronic lung disease of prematurity (BPD or CLD), or neonatal sepsis. We assessed heterogeneity via Higgins I(2) and Cochrane’s Q test, and calculated pooled odds ratios (OR) with 95% confidence intervals (CI) using random effects models. RESULTS: Sixteen observational cohort and case-control studies published from 1995–2018 met selection criteria for the systematic review and included 8,989 preterm SGA infants. ACS administration was explicitly reported among 8,376 SGA infants; 4,631 (55.3%) received ACS and 3,741 (44.7%) did not. Thirteen studies including 6,387 preterm SGA infants were then included in the meta-analysis. Neonatal mortality was significantly lower among infants who received ACS compared to those who did not (12 studies: 12.8% vs. 15.1%, pooled odds ratio [OR] 0.63 [95% CI 0.46–0.86]), with significant heterogeneity between studies (I(2)=55.1%, p=0.011). There was no significant difference in RDS (12 studies: OR 0.89 [95% CI 0.69–1.15]), NEC (7 studies: OR 0.93 [95% CI 0.70–1.22]), IVH and/or PVL (10 studies: OR 0.82 [95% CI 0.56–1.20]), BPD or CLD (8 studies: OR 1.11 [95% CI 0.88–1.41]), or neonatal sepsis (6 studies: OR 1.13 [95% CI 0.86–1.49]). CONCLUSIONS: These data show that ACS reduces neonatal mortality in SGA infants delivered preterm, with no apparent effect on neonatal morbidity. This supports the use of ACS to reduce neonatal mortality in pregnancies with SGA infants at risk for preterm birth.